Reaktualisasi Kritik KH. Misbah Musthofa dalam Tafsir Taj al-Muslimin Min Kalami Rabbil ‘Alamin terhadap Kurikulum Pendidikan di Era Orde Baru - Annisa, Ayu; Rusli, Ris'an; Edi Z, M. Khai Hanif Yuli; Hafizh, M. (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to analyze the social critique of K.H. Misbah Musthofa regarding the education curriculum during the New Order era, particularly within the context of interpreting QS. al-Baqarah [2]: 29. In this study, we delve into his perspective in detail through a content analysis approach. The data utilized is sourced from various educational and Quranic interpretation-related literature. The analysis highlights the arguments put forth by K.H. Misbah Musthofa in his critique. One crucial point emphasized is the necessity of integrating moral and spiritual values into the educational system, as well as the importance of holistic individual development. He also issues a warning about the significance of not just following contemporary trends to avoid falling behind the Western world but also preserving and perpetuating traditional values. The outcomes of this research make a significant contribution to deepening our understanding of education from an Islamic perspective. The reevaluation of KH. Misbah Musthofa's critique can serve as a foundation for formulating a more comprehensive educational approach oriented towards developing the education system, with the hope that it will contribute to building a better society.